Extremely low-frame-rate digital fluoroscopy in catheter ablation of atrial fibrillation: A comparison of 2 versus 4 frame rate. Issue 24 (June 2017) - Lee, Ji Hyun; Kim, Jun; Kim, Minsu; Hwang, Jongmin; Hwang, You Mi; Kang, Joon-Won; Nam, Gi-Byoung; Choi, Kee-Joon; Kim, You-Ho
Abstract : Abstract: Despite the technological advance in 3-dimensional (3D) mapping, radiation exposure during catheter ablation of atrial fibrillation (AF) continues to be a major concern in both patients and physicians. Previous studies reported substantial radiation exposure (7369–8690 cGy cm 2 ) during AF catheter ablation with fluoroscopic settings of 7.5 frames per second (FPS) under 3D mapping system guidance. We evaluated the efficacy and safety of a low-frame-rate fluoroscopy protocol for catheter ablation for AF. Retrospective analysis of data on 133 patients who underwent AF catheter ablation with 3-D electro-anatomic mapping at our institute from January 2014 to May 2015 was performed. Since January 2014, fluoroscopy frame rate of 4-FPS was implemented at our institute, which was further decreased to 2-FPS in September 2014. We compared the radiation exposure quantified as dose area product (DAP) and effective dose (ED) between the 4-FPS (n = 57) and 2-FPS (n = 76) groups. The 4-FPS group showed higher median DAP (599.9 cGy cm 2 ; interquartile range [IR], 371.4–1337.5 cGy cm 2 vs. 392.0 cGy cm 2 ; IR, 289.7–591.4 cGy cm 2 ; P  < .01), longer median fluoroscopic time (24.4 min; IR, 17.5–34.9 min vs. 15.1 min; IR, 10.7–20.1 min; P  < .01), and higher median ED (1.1 mSv; IR, 0.7–2.5 mSv vs. 0.7 mSv; IR, 0.6–1.1 mSv; P  < .01) compared with the 2-FPS group. No major procedure-related complications such as cardiac tamponade were observed in either group. Over follow-up durations of 331 ± 197 days, atrial tachyarrhythmia recurred in 20 patients (35.1%) in the 4-FPS group and in 27 patients (35.5%) in the 2-FPS group ( P  = .96). Kaplan–Meier survival analysis revealed no significant different between the 2 groups (log rank, P  = .25). In conclusion, both the 4-FPS and 2-FPS settings were feasible and emitted a relatively low level of radiation compared with that historically reported for DAP in a conventional fluoroscopy setting. Abstract : Supplemental Digital Content is available in the text